Flexible transparent flame‐retardant membrane based on a novel UV‐curable phosphorus‐containing acrylate. (7th August 2017) - Wang, Xiaomeng; Liu, Xueqing; Peng, Sha; Peng, Panrui; Zou, Liyong; Chen, Jia; Liu, Jiyan
Summary: A novel phosphorus‐containing acrylate monomer (AOPA) was synthesized starting from 2‐methy‐2, 5‐dioxo‐1, 2‐oxaphospholane and hydroxyethyl acrylate. The structure of AOPA was characterized with FTIR and 1 H NMR. AOPA shows good compatibility with polyethylene glycol diacrylate (PEGDA) and can polymerize with PEGDA under UV light irradiation at different mass ratios to form membranes with high transparency (above 88.9% of light transmittance in the range of 400‐800 nm) and flexibility. Incorporating 20 wt% of AOPA in PEGDA reduced the total heat release and peak rate by 50.3% and 38.4%, respectively, as measured by micro combustion calorimeter. The membrane containing 40 wt% of AOPA with 0.4 mm thickness can pass the UL94 V0 rating, and limiting oxygen index reaches 33.4%. TG‐FTIR and SEM‐EDX analysis show that the presence of AOPA depresses the thermal degradation and promotes the char formation.